2010
DOI: 10.1177/1541204010368641
|View full text |Cite
|
Sign up to set email alerts
|

Assessing School and Student Predictors of Weapons Reporting

Abstract: School violence and weapons at school are a major concern for community members, school administrators, and policy makers. This research examines both student-level and school-level variables that predict middle school students' willingness to report a weapon at school under several reporting conditions. Results substantiate previous analyses of these data that student-level variables explain students' willingness to report a weapon but extend these findings to include school climate variables that affect will… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 68 publications
0
12
0
Order By: Relevance
“…One student bystander did not come forward because he found school authorities “too judgmental,” while another student indicated that he did not tell anyone about the gun he knew was on school property because he anticipated getting into trouble or being interrogated for stepping forward (Pollack et al, 2008, p. 12). This finding is backed up by research confirming the positive correlation between cohesive, supportive, and trusting school climates and student willingness to report threats of violence in both middle and high schools (Brank et al, 2007; Brinkley & Saarnio, 2006; Fein et al, 2002; Syvertsen et al, 2009; Wylie et al, 2010) and college settings (Sulkowski, 2011).…”
Section: Contemporary School Rampage Prevention Practices and The Stumentioning
confidence: 82%
See 2 more Smart Citations
“…One student bystander did not come forward because he found school authorities “too judgmental,” while another student indicated that he did not tell anyone about the gun he knew was on school property because he anticipated getting into trouble or being interrogated for stepping forward (Pollack et al, 2008, p. 12). This finding is backed up by research confirming the positive correlation between cohesive, supportive, and trusting school climates and student willingness to report threats of violence in both middle and high schools (Brank et al, 2007; Brinkley & Saarnio, 2006; Fein et al, 2002; Syvertsen et al, 2009; Wylie et al, 2010) and college settings (Sulkowski, 2011).…”
Section: Contemporary School Rampage Prevention Practices and The Stumentioning
confidence: 82%
“…In addition to asserting the significance of Columbine as a watershed event easing the stigma against students who come forward, there was near unanimity about the appropriate methods to weaken the student code of silence; nearly all of the school and police officials expressed a firm belief in forging cohesive, supportive, and trusting school environments—views very much in sync with existing scholarship (Brank et al, 2007; Brinkley & Saarnio, 2006; Fein et al, 2002; Sulkowski, 2011; Syvertsen et al, 2009; Wylie et al, 2010). Almost without exception, respondents noted the importance of fostering an atmosphere where “students care about their school” because they “feel involved and part of the community,” and “students feel supported” and “know they can trust the adults in the building” because of “predictable and consistent” “close relationships” of “dignity and mutual respect.”…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, we included information at the school level on the percent of students receiving a free/subsidized school lunch (FSL) and size of the school population, which we obtained from the National Center for Education Statistics. These variables were included as there is mixed evidence about their association to weapons reporting and violence-related issues in schools (Eliot, Cornell, Gregory, & Fan, 2010; Wilcox & Clayton, 2001; Wylie et al, 2010).…”
Section: Methodsmentioning
confidence: 99%
“…A few studies explicitly measure school context using administrative data and by aggregating students’ perceptions to the school level. Based on data from 27 middle schools, Wylie and colleagues (2010) conclude youth are more likely to report weapons in schools with a stronger collective identity and less conflict. A second study (Eliot, Cronell, Gregory, & Fan, 2010) found that in high schools with a more supportive climate, students are more willing to seek formal help for bullying and threats of violence.…”
Section: Empirical Literaturementioning
confidence: 99%